Impact of Climate Change on Metal and Suspended Sediment Concentrations in Urban Waters - Frogner-Kockum, Paul; Göransson, Gunnel; Haeger-Eugensson, Marie (Frontiers in Environmental Science, 2020)
In order to study the impact of climate change on metal contaminant transport in urban waters and its relevance for water quality, we have analyzed variations in metal- and suspended sediment concentrations (SSC) in three urban rivers and one small creek in the Gothenburg region during various hydrological events such as spring flood, dry period and wet period. To interpret river loads of metals and SSC we have furthermore followed meteorological trends since 1961 and additionally calculated future trends for the Gothenburg region, located on the west coast of Sweden. During periods of a short-term increase in precipitation we found an increased particle bound metal transport in urban watercourses of the Göta Älv River. In addition, a correlation between studied parameters indicates that surface runoff from brownfields most likely is the main source to the increased transport of pollutants in river systems rather than re-suspension of polluted river sediment.